2020
DOI: 10.3390/molecules25020281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrafiltration of Pitaya Extract (Stenocereus thurberi) on Its Phytochemical Content, Antioxidant Capacity, and UPLC-DAD-MS Profile

Abstract: Stenocereus thurberi is an endemic species in northwestern Mexico. It produces colorful fruits called pitayas that have an edible pulp. They have phytochemical compounds associated with biological activities. Ultrafiltration is a widely used method for the clarification of fruit juices and the recovery of phytochemicals. However, its effect has not been extensively studied in extracts. Therefore, the objective of this work is to study the effect of the ultrafiltration of pitaya extract (Stenocereus thurberi) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 51 publications
2
17
0
8
Order By: Relevance
“…Heat reflux extraction was reported to decrease the bioactivity of purified polysaccharides due to the adverse effect of high temperatures, hence an ultra-high pressure enzymatic technique was used to extract polysaccharides from red pitaya peel [32]. Results showed that the main component of polysaccharides derived from red pitaya peel was a polysaccharide with 112.94 kDa average molecular mass, 17.19% degree of esterification, 97.22% water solubility, 5.51 g/g water holding capacity and 4.52 oil holding capacity.…”
Section: General Conceptsmentioning
confidence: 99%
“…Heat reflux extraction was reported to decrease the bioactivity of purified polysaccharides due to the adverse effect of high temperatures, hence an ultra-high pressure enzymatic technique was used to extract polysaccharides from red pitaya peel [32]. Results showed that the main component of polysaccharides derived from red pitaya peel was a polysaccharide with 112.94 kDa average molecular mass, 17.19% degree of esterification, 97.22% water solubility, 5.51 g/g water holding capacity and 4.52 oil holding capacity.…”
Section: General Conceptsmentioning
confidence: 99%
“…To date, there are no reports on the phytochemical composition of mandacaru fruits determined by HPLC-DAD. However, other cactus fruits have been evaluated in the literature in terms of their phytochemical profile, such as pitayas (Stenocereus thurberi, Stenocereus stellatus and Stenocereus pruinosus), which contain a series of phenolic compounds such as quercetin, ferulic acid, caffeic acid and pcoumaric acid, the latter being identified in that work (Castro-Enríquez et al, 2020;García-Cruz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The sugar content was estimated by the anthrone-sulfuric acid method (Castro-Enríquez et al, 2020). To quantify the dietary fibers, 1 g was ground and placed in a pre-weighed filter bag.…”
Section: Sugars and Dietary Fibersmentioning
confidence: 99%